Resistensi Masyarakat Terhadap Perbankan Syari’ah di Kota Langsa - Muhammad Dayyan (Faculty of Economic and Business, 2016)
The People Resistance to Islamic Banking in LangsaThe presence of Islamic Banking in Langsa since 2005 is in line with the aspirations of the Acehnese as an application of Islamic law. In this case the economic and finance tailored to the sharia is to establishe the people to be compete constructively in favor and the successful life such as happiness, glory, and the hereafter (falah). This things is to realized the shariah goal (maqashid sharia) especially in dharuriah five dimensions, such as: religion, life, thought, ancestry, and wealth. The Islamic banks has established in Langsa since 14 years ago, but the people in Langsa not yet fully trust the operational of Islamic banks. They think there is no difference between Islamic banks and conventional banks, beside using sharia label only. The people that become a conventional bank’s customer has a perception that either the Islamic banks or conventional banks still contains a riba.DOI: 10.15408/ess.v6i2.3571